An Update on the Effects of Probiotics on Gastrointestinal Cancers - Davoodvandi, Amirhossein; Fallahi, Farzaneh; Tamtaji, Omid Reza; Tajiknia, Vida; Banikazemi, Zarrin; Fathizadeh, Hadis; Abbasi-Kolli, Mohammad; Aschner, Michael; Ghandali, Maryam; Sahebkar, Amirhossein; Taghizadeh, Mohsen; Mirzaei, Hamed (Frontiers in Pharmacology, 2021)
Because of their increasing prevalence, gastrointestinal (GI) cancers are regarded as an important global health challenge. Microorganisms residing in the human GI tract, termed gut microbiota, encompass a large number of living organisms. The role of the gut in the regulation of the gut-mediated immune responses, metabolism, absorption of micro- and macro-nutrients, essential vitamins, and short-chain fatty acids production, and resistance to pathogens has been extensively investigated. In the past few decades, it has been shown that microbiota imbalance is associated with the susceptibility to various chronic disorders such as obesity, irritable bowel syndrome, inflammatory bowel disease, asthma, rheumatoid arthritis, psychiatric disorders, and various types of cancer. Emerging evidence has shown that oral administration of various strains of probiotics can protect against cancer development. Furthermore, clinical investigations suggest that probiotic administration in cancer patients decreases the incidence of post-operative inflammation. The present review addresses the efficacy and underlying mechanisms of action of probiotics against GI cancers. The safety of most commercial probiotic strains has been confirmed and therefore these strains can be used as adjuvant or neo-adjuvant treatments for cancer prevention and improving the efficacy of therapeutic strategies. Nevertheless, well-designed clinical studies are still needed for better understanding of the properties and mechanisms of action of probiotic strains in mitigating GI cancer development.